How Midwifery Education in Cyprus has Evolved in Response to the Demands of a Complex and Changing World - Hadjigeorgiou, Eleni; Christofi, Maria Dolores (My University, 2018)
Midwifery education faces rapid changes due to changing global healthcare arenas; this has created an urgent reform of midwifery education in Cyprus. The Complex System Theory (CST) raises an interesting agenda for educational change. This article refers to the CST, the findings from historical searches regarding midwifery in Cyprus and those of an original research project, in order to explore and explain the evolution of midwifery education in Cyprus. Midwifery in Cyprus continues to exist due to the reform of the midwifery education system, which includes upgrading midwifery education to Master’s-degree level.
Keywords: Midwifery education; Cyprus; Human experiment; Systems theory